E-business strategy, sourcing, and governance - Gottschalk, Petter, 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book is based on the premise that it is difficult, if not impossible, to manage a modern business or public organization without at least some knowledge of the planning, use, control and benefits of information technology"--Provided by publisher.